2000
DOI: 10.1046/j.1365-2036.2000.014s1116.x
|View full text |Cite
|
Sign up to set email alerts
|

The roles of prostaglandin E receptor subtypes in the cytoprotective action of prostaglandin E2 in rat stomach

Abstract: Aim: To investigate the EP receptor subtype involved in the gastroprotective action of prostaglandin (PG) E 2 using various EP receptor agonists in rats, and using knockout mice lacking EP 1 or EP 3 receptors. Methods: Male SD rats and C57BL/6 mice were used after an 18-h fast. Gastric lesions were induced by oral administration of HCl/ethanol (150 mM HCl in 60% ethanol). Rats were given various EP agonists i.v. 10 min before HCl/ethanol: PGE 2 , sulprostone (EP 1 /EP 3 agonist), butaprost (EP 2 agonist), 17-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 25 publications
6
77
2
3
Order By: Relevance
“…On the other hand, results of this study suggest that antagonists for either the EP 2 or EP 4 receptors, or more importantly antagonists for both EP 2 and EP 4 receptors, will be effective for the treatment and prevention of AD through inhibiting the production of A␤. EP 1 and EP 3 receptors were reported to be involved in PGE 2 -mediated protection of gastrointestinal mucosa through stimulating the production of bicarbonate and gastric mucosal blood flow, respectively (74,75). Therefore, antagonists specific for both EP 2 and EP 4 would be safer for gastrointestinal mucosa than NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, results of this study suggest that antagonists for either the EP 2 or EP 4 receptors, or more importantly antagonists for both EP 2 and EP 4 receptors, will be effective for the treatment and prevention of AD through inhibiting the production of A␤. EP 1 and EP 3 receptors were reported to be involved in PGE 2 -mediated protection of gastrointestinal mucosa through stimulating the production of bicarbonate and gastric mucosal blood flow, respectively (74,75). Therefore, antagonists specific for both EP 2 and EP 4 would be safer for gastrointestinal mucosa than NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the EP 1 receptor is mainly responsible for the gastro-protective effect of PGE 2 in vivo through the inhibition of gastric motility (37,42). In these reports, the authors examined an acute phase of gastric lesions (1 h after administration of high doses of gastric irritants), suggesting that they damaged gastric mucosal cells mainly through necrosis (not apoptosis).…”
Section: Fig 3 Effect Of Pge 2 On Ethanol-induced Release Of Cytochmentioning
confidence: 99%
“…Effect of capsaicin pretreatment on responses induced by PGE 2 , sulprostone, and ONO-AE1-329. It is believed that the acid-induced HCO 3 Ϫ secretion is mediated via an axonal reflex pathway in addition to endogenous PGs (10,19).…”
Section: Effects Of Verapamil and Ibmx On Duodenal Hcomentioning
confidence: 99%
“…The present study was designed using the selective EP4 agonist and antagonist to clarify the involvement of EP4 receptors in duodenal HCO 3 Ϫ secretion induced by PGE 2 or mucosal acidification in rats in addition to the role of EP3 receptors. We also investigated the cooperative effect of stimuli sent through EP3 and EP4 receptors on this secretion, including the intracellular signaling pathway of HCO 3 Ϫ secretion mediated by these receptors.…”
mentioning
confidence: 99%